Stasys Eidrigevičius : pastele = Stasys Eidrigevičius : pastels - Eidrigevičius, Stasys (1949- ).; Nycz, Beata; Kapuściński, Ryszard (1932-2007).; Jacobs, Michael; Wydawnictwo Buffi (Bielsko-Biała : Buffi, 1997)
Album obrazów Stasysa Eidrigevičiusa.
Bibliogr. s. 142-143.
Tekst wstępu równol. pol. ang.
Keywords: Eidrigevičius, Stasys -- (1949- ) -- katalogi; Eidrigevičius, Stasys -- (1949- ).